Mathematical Modelling of the Impact of Non-Pharmacological Strategies to Control the COVID-19 Epidemic in Portugal - Caetano, Constantino (2021)
This article belongs to the Special Issue Mathematical Biology: Developments in Epidemic and Endemic Models